Healthy Behavior and Sports Drinks: A Systematic Review - Castillo-Guajardo, D (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This review article aims to systematically identify the relationship between sports drinks and healthy behavior. This systematic literature review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline criteria, and eligibility criteria were established using the PICOS tool (population, interventions, comparators, outcomes, and study) from about 1000 records of sports drinks articles identified in the various Web of Science Core Collection databases. The literature review stages determined a reduced set of 15 articles relating these drinkable supplements to healthy behavior. This study concludes that water consumption should be emphasized for non-athletes, sports drinks should be labeled to indicate water consumption and carry a warning label, and more randomized clinical trials should be considered to ensure conclusive results for health decision making. © 2023 by the authors.